Spatial analysis of air passengers with respect to population and employment - Vedia Dokmeci; Irmak Betul Cakir (European Regional Science Association (ERSA), 1998)
The relationship between air transportation and urbanization at the national scale is investigated in order to illustrate its role in the post-war evolution of the Turkish urban system. Theory suggests that major transportation innovations have exhibited profound and prolonged interdependencies with patterns of growth in national or regional urban systems. As the most recent major intercity transportation innovation, it should be expected that utilization of air transportation should bear some relationship to patterns of growth in urban places. This paper investigates this relationship by using government air transportation data and Turkish Census data to correlate volumes of air passenger flows per capita with changes in population and employment for the 24 largest Turkish metropolitan areas and cities.The expectation that higher volumes of air passenger flow per capita exhibit a positive correlation with both previous and subsequent growth is confirmed by the analysis. At the same time, this relationship is investigated at the regional and provincial level. The results illustrate the importance of balance of air transportation and airport planning in balance urbanization and economic development of the provincies and regions. Further, especially increasing importance of Turkey's location as a result of globalisation requires the rapid and efficient development of hierarchical airport system in order to stimulate overall development and balanced urbanization.
Keywords: 330